2x-3(x+6)=-4(x+1

Simple and best practice solution for 2x-3(x+6)=-4(x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-3(x+6)=-4(x+1 equation:



2x-3(x+6)=-4(x+1
We move all terms to the left:
2x-3(x+6)-(-4(x+1)=0
We multiply parentheses
2x-3x-(-4(x+1)-18=0
We add all the numbers together, and all the variables
-1x-(-4(x+1)-18=0

See similar equations:

| 3r^2+3r-36=0 | | -15=-1x+27 | | -6(r-1)+26=14 | | p+6=p+9 | | 94=3v+22 | | -5q+8=-10+4q | | 8k+23=95 | | -3(5-2x-6+4x=9 | | 3(4)+y=-1 | | -3/4x+15=3 | | 2y+5=40 | | 5/6b=79.50 | | h+1=6h+1-5h | | 23x=-30 | | -255=3d | | 17x+21+57=180 | | 5x+71=-14 | | {2}{3}x=-30 | | 5.x-70=216-8.x | | 3f-23=10 | | 9m+3=-5 | | −2(−3x+8)=6(x+4)−3 | | 2/3(9x-6)=9 | | -4t=116 | | -4x-7(-3x-6)=135 | | -6(5k+3)=-18-k | | 3/2(8x-4)-4(2x-3)=-10 | | 360=5x+91-2x | | 21x-2=x+8 | | -2.5x-5=9 | | 2x-12=15x-4x | | 12+-v=25 |

Equations solver categories